Industrial design and manufacturing of a manual driven low cost banana / tapioca / yam slicing machine - Johnny Damian, Tawi (Universiti Malaysia Sarawak (UNIMAS), 2009)
The economic downturn is among the worst enemy to all of mankind. The unstable economy performance also causing industries to collapse especially the low and medium ranged firm. This would much affect the increment of food prices and all groceries that available in the market. This would tighten up our budget and might as well affect our health and lifestyle indirectly. Many has turn to home-cook meals instead of going to food stall and putting an extra ringgit on packet food which not so healthy. Hence, the purpose of this project is to design of a manual driven low cost banana, yam, or tapioca slicing machine. Most of the food processor available in the market is imported and costly as well. For this project, this food slicing machine will be able to be much applied for fresh food such as fruits and vegetables. This would create a good eating habit and cost less compared to fast food. The development for this machine begins by indentifying problems that occurs. Then, studies on the food processor available in the market as well foods which are directly related are next in line. Then only the machine is design based on the concept adapted from the problems. Next, careful material selection process begins in order to make sure the material used is safe for user. Next process which is comparison of the forcasted performance between various types of slicing are done and followed by the discussion and recommendation process.